Improving the accuracy of Laplacian estimation with novel multipolar concentric ring electrodes. (February 2016) - Makeyev, Oleksandr; Ding, Quan; Besio, Walter G.
Highlights: Estimation of surface Laplacian for multipolar concentric ring electrode is derived. Derivation is based on inversion of a square Vandermonde matrix. Accuracy of Laplacian estimate increases with the increase of the number of rings. Finite element method model analysis is performed to confirm the analytic results. Concentric ring electrode configurations with 1–6 rings are directly compared. Abstract: Conventional electroencephalography with disc electrodes has major drawbacks including poor spatial resolution, selectivity and low signal-to-noise ratio that are critically limiting its use. Concentric ring electrodes, consisting of several elements including the central disc and a number of concentric rings, are a promising alternative with potential to improve all of the aforementioned aspects significantly. In our previous work, the tripolar concentric ring electrode was successfully used in a wide range of applications demonstrating its superiority to conventional disc electrode, in particular, in accuracy of Laplacian estimation. This paper takes the next step toward further improving the Laplacian estimation with novel multipolar concentric ring electrodes by completing and validating a general approach to estimation of the Laplacian for an ( n  + 1)-polar electrode with n rings using the (4 n  + 1)-point method for n  ⩾ 2 that allows cancellation of all the truncation terms up to the order of 2 n . An explicit formula based on inversion of a square Vandermonde matrix is derived to make computation of multipolar Laplacian more efficient. To confirm the analytic result of the accuracy of Laplacian estimate increasing with the increase of n and to assess the significance of this gain in accuracy for practical applications finite element method model analysis has been performed. Multipolar concentric ring electrode configurations with n ranging from 1 ring (bipolar electrode configuration) to 6 rings (septapolar electrode configuration) were directly compared and obtained results suggest the significance of the increase in Laplacian accuracy caused by increase of n .